The role of calcium and vitamin D dietary intake on risk of colorectal cancer: systematic review and meta-analysis of case–control studies - Lopez-Caleya, Juan Francisco; Ortega-Valín, Luis; Fernández-Villa, Tania; Delgado-Rodríguez, Miguel; Martín-Sánchez, Vicente; Molina, Antonio José (Cancer causes & control, 2022)
Purpose The aim of this study is to analyze the current evidence about the relationships between calcium/vitamin D and CRC based on case–control studies according to sex, tumor location and continental region to complement the information obtained in meta-analyses of other designs. Methods The articles were located in three databases (PUBMED, EMBASE and SCOPUS), they should be written in English language, with a case and control design and published between 1 January 1970 and 31 October 2019. Results There were 37 selected studies, 32 for intake of calcium, that involved 24,353 CRC cases and 30,650 controls, and 23 for that of VIT D, with a total of 19,076 cases and 36.746 controls included. For dietary calcium intake, the overall OR was 0.94 (95% CI 0.92–0.97), suggesting a reducing effect with a 6% decrease in CRC risk for every 300 mg of calcium ingested daily. Regarding vitamin D intake a global OR of 0.96 (95% CI 0.93–0.98) was observed, what means a 4% decrease in the risk of CRC per 100 IU/day of vitamin D. Conclusion Higher dietary intakes of calcium and vitamin D are associated to a decreased risk of CRC.